2008
DOI: 10.1590/s0074-02762008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Triatoma vitticeps (Stål, 1859) in Itanhomi, Minas Gerais, Brazil

Abstract: (Galvão et al. 2003, Galvão & Angulo 2006, Costa et al. 2006, Costa & Felix 2007, Sandoval et al. 2007, Bérenger & Blanchet 2007, Martinez et al. 2007) and is a vector of Trypanosoma cruzi. Its geographical distribution is limited to the Brazilian states of Bahia, Espírito Santo, Minas Gerais (MG), and Rio de Janeiro (Galvão et al. 2003). Although considered to be of secondary importance in T. cruzi transmission to man, this species shows high rates of trypanosome infection (Santos et al. 1969a,c, Pinto et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
15
1
2
Order By: Relevance
“…Today, field data have shown that the following sylvatic species are frequently found in domiciliary and peridomiciliary areas: Triatoma vitticeps (Stål, 1859), Triatoma rubrovaria (Blanchard, 1843) and Panstrongylus lutzi (Neiva & Pinto, 1923) (Gonçalves et al 1998, Almeida et al 2000, Freitas et al 2004, Souza et al 2008, among others. More recently, Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata 2002 was captured in Gentio do Ouro, in the north central part of BA, colonising human dwellings (Almeida et al 2009, unpublished observations).…”
Section: Biology Diversity and Strategies For The Monitoring And Conmentioning
confidence: 99%
“…Today, field data have shown that the following sylvatic species are frequently found in domiciliary and peridomiciliary areas: Triatoma vitticeps (Stål, 1859), Triatoma rubrovaria (Blanchard, 1843) and Panstrongylus lutzi (Neiva & Pinto, 1923) (Gonçalves et al 1998, Almeida et al 2000, Freitas et al 2004, Souza et al 2008, among others. More recently, Triatoma sherlocki Papa, Jurberg, Carcavallo, Cerqueira & Barata 2002 was captured in Gentio do Ouro, in the north central part of BA, colonising human dwellings (Almeida et al 2009, unpublished observations).…”
Section: Biology Diversity and Strategies For The Monitoring And Conmentioning
confidence: 99%
“…The high rate of positivity for T. cruzi fl agellates was similar to what has been described in other areas where this species is present. Several studies have demonstrated the high dispersion capacity of T. vitticeps, primarily in the States of Espírito Santo, Minas Gerais, Rio de Janeiro and Bahia [22][23][24] . Other authors have confi rmed high rates of natural infection with T. cruzi, with a rate of positivity between 25% and 65% of insects examined [24][25][26][27] .…”
Section: Epidemiological Evaluationmentioning
confidence: 99%
“…Several studies have demonstrated the high dispersion capacity of T. vitticeps, primarily in the States of Espírito Santo, Minas Gerais, Rio de Janeiro and Bahia [22][23][24] . Other authors have confi rmed high rates of natural infection with T. cruzi, with a rate of positivity between 25% and 65% of insects examined [24][25][26][27] . Curiously, in the State of Espírito Santo where the frequency of T. vitticeps and positivity for T. cruzi is higher in rural dwellings, the prevalence of Chagas disease is low and limited to autochthonous cases of transmission by this species 28 .…”
Section: Epidemiological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…106(1): 16-22, February 2011 Triatoma vitticeps is a triatominae species found in the Brazilian states of Espírito Santo (ES), Minas Gerais (MG), Rio de Janeiro (RJ) and the southernmost regions of Bahia (Lent & Wygodzinsky 1979, Silveira et al 1984. Studies carried out on T. vitticeps populations in ES, RJ and MG demonstrated the capacity of this triatomine to invade houses (Santos et al 1969c, Ferreira et al 1986, Sessa & Carias 1986, Dias et al 1989, Gonçalves et al 1998, Souza et al 2008. Similarly, these invasive insects were always highly infected with flagellates similar to Trypanosoma cruzi (Pinto et al 1969, Santos et al 1969a, b, Barros et al 1975, Sessa & Carias 1986, Dias et al 1989, Gonçalves et al 1998, dos Santos et al 2005.…”
mentioning
confidence: 99%